2020
DOI: 10.1111/risa.13531
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Belief in Personal Capability: Antecedents of Self‐Efficacy in Private Adaptation to Flood Risk

Abstract: Self-efficacy is one of the strongest and most consistent drivers of private flood mitigation behavior; however, the factors influencing self-efficacy in the context of flooding remain unclear. The present study examines three potential antecedents of self-efficacy: personal and vicarious experiences of floods or building-related events, social norms for private flood preparedness, and personal competencies such as technical abilities and social skills. While controlling for other drivers in a protection motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 58 publications
2
35
3
Order By: Relevance
“…Both sets of actors would suffer from the same issue, limiting its overall impact on our core research question. Moreover, this issue could be further limited as recent research has indicated that many perceptions remain rather constant overtime, at least in the absence of a flood (Bubeck et al, 2020;Seebauer and Babcicky (2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Both sets of actors would suffer from the same issue, limiting its overall impact on our core research question. Moreover, this issue could be further limited as recent research has indicated that many perceptions remain rather constant overtime, at least in the absence of a flood (Bubeck et al, 2020;Seebauer and Babcicky (2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Most studies have demonstrated that high self-efficacy can motivate disaster preparedness intentions or the actual behaviors [ 30 , 34 , 35 ], or the specific protective actions in emergencies such as emergency evacuation [ 29 ]. Such positive effects were primarily observed in preparation for floods [ 36 , 37 , 38 , 39 ], earthquakes [ 40 ], or climate change-related hazards [ 30 ]. In household disaster preparedness studies, self-efficacy is always captured by the self-reported confidence of their capacity for implementing a protective action against a disaster or successfully coping with potential disasters [ 33 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such positive effects were primarily observed in preparation for floods [ 36 , 37 , 38 , 39 ], earthquakes [ 40 ], or climate change-related hazards [ 30 ]. In household disaster preparedness studies, self-efficacy is always captured by the self-reported confidence of their capacity for implementing a protective action against a disaster or successfully coping with potential disasters [ 33 , 39 ]. It appears that the role of self-efficacy in disaster preparedness is still relatively understudied in terms of geographical, social and cultural diversity, though there is an increasing trend in recent years [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…There may be different ways of coping with a threatening situation that do not all result in an increase in the uptake of precautionary measures or adaptation [7]. This can include factors such as worry [47,54] or trust in structural protection [58,67]. For example, Hanger et al [21] found that respondents in Austria and England that are protected by public structural measures are less likely to take private precautionary measures.…”
Section: The Motivation For the Uptake Of Private Precautionary Measuresmentioning
confidence: 99%
“…A pilot project that provided funding for surveys and measures helped people to choose the correct measures and increased the uptake of private precaution [22]. A study in Canada highlights the importance of considering the difference between the general intention to implement private precautionary measures and the willingness to implement individual measures [58]. The former is more influenced by fear and risk perception, while the latter instead depends more on the perceived response efficacy and costs [58].…”
Section: The Motivation For the Uptake Of Private Precautionary Measuresmentioning
confidence: 99%